Lighting Scheme as a Design Tool in Urban Identity: A Case Study at Bosphorus Region in Istanbul - Kutlu, Rana; Manav, Banu (My University, 2013)
City lighting influence people’s aesthetic perception, enhance the quality of people’s lives. At the same time, it can promote development of the city, enhance the reputation of the city, has the profound significance to politics, the economy and the culture. Good lighting design can display the culture and the characteristic of the city and build a charm light world. Istanbul is one of the most important cultural, historical and commercial centers of the world. In the case study, historical and contemporary regions in Istanbul through the Bosphorus Strait will be discussed and analyzed considering lighting scheme as a “design tool” in the lighting master plan. Bosphorus region is selected for the lighting analyze because of having symbolic characteristics of the city. Lighting scheme will be analyzed according to the “holistic design approach”. From this point of view, lighting scheme must include all the components of outdoor urban environment, maximizing the value of the night and minimizing all potential adverse effects. The urban lighting conditions will be analyzed through a checklist and preferences of users will be evaluated through a questionnaire.
Keywords: Light Mapping; Visual Culture; Image of the City; Urban Identity; Istanbul-Bosphorus